Respuesta :
Answer:
The equation of the circle is [tex](x+2)^2+(y-1)^2=25[/tex]
Step-by-step explanation:
we know that
The equation of a circle in standard form is equal to
[tex](x-h)^2+(y-k)^2=r^2[/tex]
where
(h,k) is the center
r is the radius
step 1
Find the radius of the circle
The radius of the circle is equal to the distance from the center to any point on the circle
we have
(–5, –3) and (–2, 1)
Find the distance
the formula to calculate the distance between two points is equal to
[tex]d=\sqrt{(y2-y1)^{2}+(x2-x1)^{2}}[/tex]
substitute
[tex]r=\sqrt{(1+3)^{2}+(-2+5)^{2}}[/tex]
[tex]r=\sqrt{(4)^{2}+(3)^{2}}[/tex]
[tex]r=\sqrt{25}[/tex]
[tex]r=5\ units[/tex]
step 2
Find the equation of the circle
we have
[tex]r=5\ units[/tex]
[tex](h,k)=(-2,1)[/tex]
substitute
[tex](x-h)^2+(y-k)^2=r^2[/tex]
[tex](x+2)^2+(y-1)^2=5^2[/tex]
[tex](x+2)^2+(y-1)^2=25[/tex]
therefore
The equation of the circle is [tex](x+2)^2+(y-1)^2=25[/tex]
Answer:
(x + 2) 2 + (y – 1) 2 = 25
Step-by-step explanation:
I took it on the edg test and got it right!!